2019
DOI: 10.1021/acsnano.9b00278
|View full text |Cite
|
Sign up to set email alerts
|

Altering the Properties of Graphene on Cu(111) by Intercalation of Potassium Bromide

Abstract: The catalytic growth on transition metal surfaces provides a clean and controllable route to obtain defect-free, monocrystalline graphene. However, graphene’s optical and electronic properties are diminished by the interaction with the metal substrate. One way to overcome this obstacle is the intercalation of atoms and molecules decoupling the graphene and restoring its electronic structure. We applied noncontact atomic force microscopy to study the structural and electric properties of graphene on clean Cu(11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 62 publications
7
28
0
Order By: Relevance
“…Clusters of three KBr units are periodically formed to minimize the overall adsorption energy. The calculated adsorption energy for the 12 × and for the larger 12 × 2 configuration is in both cases −5.31 eV/nm 2 (−0.82 eV/unit, the adsorption energy in a unit cell) and thus stronger than on Cu(111), where it was −2.43 eV/nm 2 [ 18 ]. Calculation of the specific adsorption energies of K and Br and their distance from the Ir surface at the equilibrium geometry revealed that fcc or hcp threefold hollow sites are more favorable for the adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clusters of three KBr units are periodically formed to minimize the overall adsorption energy. The calculated adsorption energy for the 12 × and for the larger 12 × 2 configuration is in both cases −5.31 eV/nm 2 (−0.82 eV/unit, the adsorption energy in a unit cell) and thus stronger than on Cu(111), where it was −2.43 eV/nm 2 [ 18 ]. Calculation of the specific adsorption energies of K and Br and their distance from the Ir surface at the equilibrium geometry revealed that fcc or hcp threefold hollow sites are more favorable for the adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4a shows a large-area topography of the Ir(111) surface, half of which is covered by graphene and additionally less than one monolayer of KBr. For Cu(111), KBr intercalation, which induces a decoupling of the graphene layer from the metal substrate, was observed with a similar preparation [ 18 ]. Here, different types of KBr patterns are found in separated regions with and without graphene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary computational results indicate that three additional electrons injected in the N‐KG would promote a ferromagnetic state (see Figure S8). Although local charging of individual π‐extended tetraazapentacenes (the electron‐poor counterpart of the semiconductor pentacene) [37] is experimentally possible by tip gating (Figure S3), [38] such quantum phase transition would require to electronically decouple the entire N‐KG from the metallic substrate [39] …”
Section: Methodsmentioning
confidence: 99%
“…to electronically decouple the entire N-KG from the metallic substrate. [39] In summary, we employed an Ullmann coupling reaction for the bottom-up synthesis of N-doped Kagome graphene on Ag(111). The reaction of linear ditopic TBQP precursors is steered by an organometallic intermediate leading to triangular nodes and a long-range honeycombed Kagome lattice.…”
Section: Zuschriftenmentioning
confidence: 99%